The politics of selfhood : bodies and identities in global capitalism - Brown, Richard Harvey (Public worlds, 2003)
Taking a cross-cultural approach, the authors consider how the body is constructed in various ways for different purposes, how the electronic media shapes selves and sensualities and contributes to civic discourse, and how global capitalism acts as a force in these processes.